Low-firing, temperature stable and improved microwave dielectric properties of ZnO-TiO2-Nb2O5 composite ceramics - Yang, Hongyu; Zhang, Shuren; Chen, Yawei; Yang, Hongcheng; Fang, Zixuan; Yuan, Ying; Li, Enzhu (Journal of Materiomics, 2019)
This article presents low-firing, low-loss and temperature stable ZnOTiO2Nb2O5 microwave dielectric composite ceramics with the assistance of lithium borosilicate (LBS) and zinc borosilicate (ZBS) glass frits. There is a liquid phase (eutectic mixture) generated by LBS (ZBS) glass, and solid particles could be wetted and dissolved. Therefore, the migrations and rearrangements of particles could be performed. Besides, compared with ceramics undoped with glass frits, lower activation energies (Ea) of ceramics doped with LBS and ZBS glass suggest that the low-temperature sintering behavior is easier to carry out. The results indicated that LBS and ZBS glass both are effective sintering aids to accelerate the sintering process and improve the microwave dielectric properties of composite ceramics by controlling the phase compositions under low temperature. Combination great properties of ZnOTiO2Nb2O5 ceramics were obtained when sintered at 900 °C for 4 h: εr = 36.7, Q × f = 20,000 GHz, τf = 7 ppm/oC. Keywords: ZnO-TiO2Nb2O5, Composite ceramics, Dielectric